Judicial Consequentialism in the process and tax enforcement (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The present work aims to propose a legal adequacy of judicial consequentialism, outlining the acceptable limits of the judge’s action when he brings to the judicial decision the factual elements of reality and in what way these can legally broaden or restrict the scope in the legal norm, particularly in the Tax Procedural Law, in order to expose the extra juridical elements that interfere in the formation of the judicial decision, mainly the economic data, testing the proposition, in the end, in two examples: statute of limitations in judicial tax foreclosure process and the recent interpretation of art. 40 by the Superior Court of Justice and the possibility for the judge to require the judicial deposit of the amount of the tax discussed as a condition to grant early protection in tax matters before an economic agent that operates in the sector of distribution of fuels, natural gas and biofuels.
Keywords: Interpretation and application of law; Positivism; Judicial consequentialism; Tax process; Judicial tax foreclosure process; Statute of limitations on judicial process; Suspensive causes of tax credit enforcement